Associations of oxygenated hemoglobin with disease burden and prognosis in stable COPD: results from COSYCONET - Trudzinski, Franziska; Jörres, R. A.; Alter, P.; Kahnert, K.; Waschki, B.; Herr, C.; Kellerer, C.; Omlor, A.; Vogelmeier, C. F.; Fähndrich, S.; Watz, H.; Welte, Tobias; et al. (Scientific reports, 2020)
We studied whether in patients with stable COPD blood gases (BG), especially oxygenated hemoglobin (OxyHem) as a novel biomarker confer information on disease burden and prognosis and how this adds to the information provided by the comorbidity pattern and systemic inflammation. Data from 2137 patients (GOLD grades 1-4) of the baseline dataset of the COSYCONET COPD cohort were used. The associations with dyspnea, exacerbation history, BODE-Index (cut-off ≤2) and all-cause mortality over 3 years of follow-up were determined by logistic and Cox regression analyses, with sex, age, BMI and pack years as covariates. Predictive values were evaluated by ROC curves. Capillary blood gases included SaO2, PaO2, PaCO2, pH, BE and the concentration of OxyHem [haemoglobin (Hb) x fractional SaO2, g/dL] as a simple-to-measure correlate of oxygen content. Inflammatory markers were WBC, CRP, IL-6 and -8, TNF-alpha and fibrinogen, and comorbidities comprised a broad panel including cardiac and metabolic disorders. Among BG, OxyHem was associated with dyspnoea, exacerbation history, BODE-Index and mortality. Among inflammatory markers and comorbidities, only WBC and heart failure were consistently related to all outcomes. ROC analyses indicated that OxyHem provided information of a magnitude comparable to that of WBC, with optimal cut-off values of 12.5 g/dL and 8000/µL, respectively. Regarding mortality, OxyHem also carried independent, additional information, showing a hazard ratio of 2.77 (95% CI: 1.85-4.15, p < 0.0001) for values <12.5 g/dL. For comparison, the hazard ratio for WBC > 8000/µL was 2.33 (95% CI: 1.60-3.39, p < 0.0001). In stable COPD, the concentration of oxygenated hemoglobin provided additional information on disease state, especially mortality risk. OxyHem can be calculated from hemoglobin concentration and oxygen saturation without the need for the measurement of PaO2. It thus appears well suited for clinical use with minimal equipment, especially for GPs.
Gesehen am 17.09.2020